2015
DOI: 10.4184/asj.2015.9.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Topical Gelatin-Thrombin Matrix Sealant in Reducing Postoperative Drainage Following Anterior Cervical Discectomy and Fusion

Abstract: Study Design:Retrospective fusion level(s)-, age-, and gender-matched analysis. Purpose: To determine whether the application of a topical gelatin-thrombin matrix sealant (Floseal) at the end of anterior cervical discectomy and fusion (ACDF) can reduce the amount of postoperative hemorrhage. Overview of Literature: The effect of the matrix sealant in decreasing postoperative hemorrhage following ACDF has not been reported. Methods: Matrix sealant was (n=116, study group) or was not applied (n=58, control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…e effectiveness of FLOSEAL, which is a topical hemostatic agent containing a flowable gelatin bovine matrix and a human-derived thrombin component, has been shown in various types of operations [1][2][3][4]6,9,11,[13][14][15]16,20] . However, no reports have evaluated the effectiveness of FLOSEAL objectively in the neurosurgical field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e effectiveness of FLOSEAL, which is a topical hemostatic agent containing a flowable gelatin bovine matrix and a human-derived thrombin component, has been shown in various types of operations [1][2][3][4]6,9,11,[13][14][15]16,20] . However, no reports have evaluated the effectiveness of FLOSEAL objectively in the neurosurgical field.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of a reduction in postoperative bleeding in the FLOSEAL group is consistent with the previous reports in orthopedics or adenotonsillectomy. [9,11,23] As a result of reduced postoperative bleeding, patients may have little risk for reoperation for postoperative hemorrhage or for having complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjunctive use of flowable gelatin-thrombin hemostat (Floseal) has been shown to reduce both intraoperative blood loss (by 30%) and postoperative decrease in hemoglobin concentration in adolescents undergoing posterior spinal fusion for idiopathic scoliosis [ 69 ]. Application of Floseal at the end of anterior cervical discectomy and fusion has also been shown to significantly reduce occurrence of postoperative hemorrhage [ 70 ]. Analysis of 2 flowable hemostats found that surgery time, risk of blood transfusion, and amount of hemostat used is lower with Floseal patients in comparison to Surgiflo [ 71 ].…”
Section: Approaches To Managing Bleeding In Spine Surgerymentioning
confidence: 99%
“…Gelatin sponge has been proved to be safe because of the low antigenicity of gelatin-based hemostatic agents, and skin, horn, and hoof materials from pigs and cows are easily accepted by the human body. 5 However, these hemostatic methods, including gelatin sponge, may be ineffective and impractical in locations that are deep and difficult to access, and for irregularly shaped wounds, bleeding lesions near important and vulnerable tissues, and diffuse capillary and venous plexus bleeding, especially during spinal surgery, 6,7 neurosurgery, 8,9 cardiovascular surgery, 10,11 urology, 12 gynecology, 13,14 and other surgical specialties. Surgeons thus require suitable hemostatic agent for these situations.…”
mentioning
confidence: 99%